ULCER PROTECTIVE ACTIVITY OF GUNMATHI CHOORANAM ON PYLORIC LIGATED METHOD - S. ARULSORUBI; P.PARTHIBAN; K. KANAGAVALLI; J. ANBU; ASHWINI ANJANA (International Journal of Pharma and Bio Sciences, 2012)
The present investigation was undertaken is to explore the antiulcer activity of the Gunmathi Chooranam in rats by pyloric ligation method. The experimental parameters used were ulcer index, gastric pH parameters. The animals groups were divided in five controls, standard (Ranitidine 100 mg/kg) and Gunmathi Chooranam in 125, 250 and 500 mg/kg. The siddha formulation produced the significant action against the antiulcer group’s animal in all parameters. The Gunmathi Chooranam was found to be good antiulcer drug in siddha system.